2023
DOI: 10.3390/plants12020286
|View full text |Cite
|
Sign up to set email alerts
|

Annotation of the Turnera subulata (Passifloraceae) Draft Genome Reveals the S-Locus Evolved after the Divergence of Turneroideae from Passifloroideae in a Stepwise Manner

Abstract: A majority of Turnera species (Passifloraceae) exhibit distyly, a reproductive system involving both self-incompatibility and reciprocal herkogamy. This system differs from self-incompatibility in Passiflora species. The genetic basis of distyly in Turnera is a supergene, restricted to the S-morph, and containing three S-genes. How supergenes and distyly evolved in Turnera, and the other Angiosperm families exhibiting distyly remain largely unknown. Unraveling the evolutionary origins in Turnera requires the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 107 publications
2
5
0
Order By: Relevance
“…This result corroborates previous studies that found an overall decrease in genetic diversity between the S-locus and its flanking regions in Primula (Potente, Léveillé-Bourret, et al, 2022), Linum (Gutiérrez-Valencia et al, 2022), and Turnera (Henning et al, 2023). Thus, our work confirms predictions that S-locus genomic architecture influences patterns of molecular evolution in S-genes.…”
Section: Population Genetic Consequences Of Hemizygosity and Transiti...supporting
confidence: 93%
“…This result corroborates previous studies that found an overall decrease in genetic diversity between the S-locus and its flanking regions in Primula (Potente, Léveillé-Bourret, et al, 2022), Linum (Gutiérrez-Valencia et al, 2022), and Turnera (Henning et al, 2023). Thus, our work confirms predictions that S-locus genomic architecture influences patterns of molecular evolution in S-genes.…”
Section: Population Genetic Consequences Of Hemizygosity and Transiti...supporting
confidence: 93%
“…However, in P. veris (Potente et al ., 2022a), Ty3‐Gypsy retrotransposons are not preferentially accumulated at the S ‐locus, only Ty1‐Copia elements were identified (Table S8). In T. subulata (Henning et al ., 2023) and F. esculentum (Yasui et al ., 2016), both Ty1 ‐ Copia and Ty3‐Gypsy were identified (see Table S8).…”
Section: Resultsmentioning
confidence: 99%
“…We identified repetitive elements in the assembly using R epeat M asker v.4.1.0 (http://www.repeatmasker.org) with the de novo repeat library built with R epeat M odeler v.2.0.1 (http://www.repeatmasker.org) and the Repbase database (http://www.girinst.org/repbase/). Additionally, we used E dta v.1.9.7 (Ou et al ., 2019), an automated whole‐genome de novo transposable element (TE) annotation software, for the de novo prediction of TEs in the S‐morph genomes of N. indica , P. veris (Potente et al ., 2022a), T. subulata (Henning et al ., 2023), L. tenue (Gutierrez‐Valencia et al ., 2022), and F. esculentum (Yasui et al ., 2016). This analysis focused exclusively on the S‐morph, and the L‐morph was not included.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations